Naringina atenua a injúria de isquemia – reperfusão cardíaca por mecanismos que envolvem a via anti-apoptótica e ação do KATP - Araujo, Andreza Melo de (2022)
Introduction: acute myocardial infarction (AMI) remains with high morbidity and mortality rates and occurs mainly due to reduced blood flow due to atherosclerotic plaque leading to ischemia. Although reperfusion is the main clinical intervention, it exacerbates damage initiated during ischemia. Therefore, natural products have been studied for the prevention and treatment of AMI. Naringin (NRG) is a flavonoid found in citrus fruits with recognized cardioprotection against atherosclerosis, coronary disease, hypertension, cardiac hypertrophy, AMI and ischemic stroke. Objective: to elucidate the mechanism of NRG in cardioprotection against IR injury. Methods: in isolated hearts of Wistar rats, the effects of NRG (5 and 10 µM) on contractile and electrocardiographic variables were evaluated. Isolated hearts were perfused with NRG (5 µM) or NRG with glibenclamide (GLI, 10 µM, a non-specific blocker of KATP channels) and subjected to global ischemia (30 min) and reperfusion (60 min). The area of infarction, tissue injury through the release of lactate dehydrogenase (LDH), index and occurrence of arrhythmias and contractile variables were evaluated. In animals pre-treated for 7 days (NRG 25 mg/kg or N-acetyl cysteine 100 mg/kg) and submitted to the IR protocol, the expression of Bax, Blc-2, SOD CuZn and SOD Mn were evaluated. In addition, citrate synthase activity and histological changes were analyzed. Results: When NRG was perfused at 5 or 10 µM concentrations, it did not change contractile and electrocardiographic variables in isolated hearts. The cardioprotective effect of NRG (5 µM) was abolished in the presence of GLI, since there was a decrease in LVDP, an increase in tissue injury (LDH) and infarcted area, an increase in the rate of arrhythmias and in the occurrence of more severe arrhythmias (tachycardia and ventricular fibrillation). In animals treated with NRG and submitted to IR, there was a decrease in Bax expression and in the Bax/Bcl-2 ratio compared to the vehicle + IR group. There was no alteration in the expression of SOD CuZn and SOD Mn among the four groups studied, in addition, in the hearts of animals pre-treated with NRG there was an increase in citrate synthase activity. Histopathological analysis showed that NRG decreased intracellular and interstitial edema and prevented changes in nuclear and cytoplasmic diameter. Conclusion: this study demonstrates that NRG has a cardioprotective effect against cardiac IR injury mediated by its anti-apoptotic, antiarrhythmic action and probable activation of KATP. In addition, it provides subsidies for future studies that can ensure the use of medicinal plants, natural products and foods rich in NRG in cardioprotection against AMI.